The token economy as a key driver for tourism: Entering the next phase of blockchain research. (November 2021) - Treiblmaier, Horst
Abstract: This is a research note in which I briefly outline the advantages of discussing tokens in tourism research rather than referring to the rather unspecific terms "cryptocurrencies" or "blockchain". Highlights: Blockchain is gaining popularity in tourism research but is poorly defined. A token classification scheme is presented that describes blockchain applications. Three main questions are suggested that should be reported in every blockchain study.